2018
DOI: 10.1038/s41467-018-03381-y
|View full text |Cite
|
Sign up to set email alerts
|

Intersubband plasmons in the quantum limit in gated and aligned carbon nanotubes

Abstract: Confined electrons collectively oscillate in response to light, resulting in a plasmon resonance whose frequency is determined by the electron density and the size and shape of the confinement structure. Plasmons in metallic particles typically occur in the classical regime where the characteristic quantum level spacing is negligibly small compared to the plasma frequency. In doped semiconductor quantum wells, quantum plasmon excitations can be observed, where the quantization energy exceeds the plasma frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 39 publications
2
69
0
Order By: Relevance
“…Senga et al showed consistent absorption peaks for isolated metallic SWNTs that are unintendedly doped on the TEM supporting grid during electron * daria.satco@skoltech.ru † nugraha@flex.phys.tohoku.ac.jp energy-loss spectroscopy (EELS) measurement [22,23]. Yanagi et al proposed that the absorption peaks are related with intersubband plasmon excitations [21], i.e., the optical transitions with energies E ij occur collectively between two electronic subbands i and j as a response to the perpendicularly polarized light. Unlike the interband excitations E ii which take place from the valence to the conduction bands, the intersubband plasmon excitations E ij occur within the conduction band or within the valence band.…”
Section: Introductionmentioning
confidence: 99%
“…Senga et al showed consistent absorption peaks for isolated metallic SWNTs that are unintendedly doped on the TEM supporting grid during electron * daria.satco@skoltech.ru † nugraha@flex.phys.tohoku.ac.jp energy-loss spectroscopy (EELS) measurement [22,23]. Yanagi et al proposed that the absorption peaks are related with intersubband plasmon excitations [21], i.e., the optical transitions with energies E ij occur collectively between two electronic subbands i and j as a response to the perpendicularly polarized light. Unlike the interband excitations E ii which take place from the valence to the conduction bands, the intersubband plasmon excitations E ij occur within the conduction band or within the valence band.…”
Section: Introductionmentioning
confidence: 99%
“…We employed the recently reported controlled vacuum filtration method 13 to fabricate wafer-scale singledomain thin films of aligned SWCNTs. By using the electrolyte gating method, 4,12,14 we systematically varied the E F of the SWCNT thin film in a wide range, observing a sign change in S when the system goes from the p-type region to the n-type region. The value of r showed strong in-plane anisotropy, i.e., more conducting in the direction parallel to a)…”
mentioning
confidence: 99%
“…We anticipate that this near-field approach will also enable explorations of strong and ultrastrong light-matter coupling in the single nanoantenna regime for other excitations. 44,45 This approach also holds a great potential for probing nano-scale quantum systems positioned not only on the surface, [25][26][27]35 but also buried within a depth of over one hundred nanometers. For example, a small non-resonant nanoantenna may extend the reach of s-SNOM deeper below the surface and enable spectroscopy of ISB transitions in QWs without strong coupling.…”
Section: Schematics Of the Qw Potential Profile Is Shown Inmentioning
confidence: 99%